Testicular tumors in the “elderly” population - Secondino, Simona; Rosti, Giovanni; Tralongo, Antonino C.; Nolè, Franco; Alaimo, Domiziana; Carminati, Ornella; Naspro, Richard Lawrence John; Pedrazzoli, Paolo (Frontiers in Oncology, 2022)
Germ cell tumors arise in childhood but peak at around 30 years of age. They are the most common cancers in males under the age of 35. Over 95% arise in the testes while a minority originate in extragonadal sites such as the anterior mediastinum, or mainly in childhood the pineal gland or the sacrococcygeal area. These tumors show an extraordinary sensitivity to chemotherapy (and for seminoma, also to radiation) and cure rates are relatively high even in second or subsequent relapses. Very few data are present in the literature regarding patients diagnosed after 50 years and no specific trials have been conducted in this setting. Nearly all patients reported in the literature had testicular cancers, with occasional reports of extragonadal tumors. Despite the fact that > 50 years may be considered an “elderly” population, these patients are treated with the same cisplatin containing combination as their younger counterparts with consequent higher toxicity. In this review we will present epidemiological and clinical data from this rare population of patients with testicular cancer.